2008
DOI: 10.1080/13825580802233426
|View full text |Cite
|
Sign up to set email alerts
|

Differential Age Effects in Load-Dependent Memory Processing

Abstract: This study examined differential age effects in a young and a middle-aged sample by means of a sequential n-back task with increasing memory load. Participants processed two streams of stimuli either separately as a single task, or simultaneously as a dual task. We investigated age effects as a function of memory load in both the single and the dual-task version. In accuracy, we observed differential age effects as a function of load, which were more prominent in the dual-compared to the single-task versions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 76 publications
2
25
0
Order By: Relevance
“…This dual-task component distinguishes it from training interventions previously studied in older adults as they have used WM training tapping only one modality at once (visual or auditory). In our view, a more complex training paradigm would be more apt to balance out adult age differences, as studies have shown age differences to be more prominent in more complex tasks (Jaeggi, Schmid et al, 2008;Salthouse, 1992;Voelcker-Rehage et al, 2006). In a previous study with young adults we found transfer effects after dual n-back training to several executive functions including WM updating, task switching, and inhibition in attentional processes .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This dual-task component distinguishes it from training interventions previously studied in older adults as they have used WM training tapping only one modality at once (visual or auditory). In our view, a more complex training paradigm would be more apt to balance out adult age differences, as studies have shown age differences to be more prominent in more complex tasks (Jaeggi, Schmid et al, 2008;Salthouse, 1992;Voelcker-Rehage et al, 2006). In a previous study with young adults we found transfer effects after dual n-back training to several executive functions including WM updating, task switching, and inhibition in attentional processes .…”
Section: Discussionmentioning
confidence: 88%
“…In a study comparing age effects in single n-back performance (VS or AV n-back task) and dual n-back performance (VS and AV n-back task) without training, Jaeggi, Schmid, Buschkuehl, and Perrig et al (2008) showed that the age effects were specifically prominent in the dual n-back version. That is, the older participants showed a significantly impaired performance in the dual n-back but not in the single n-back tasks, compared with the young adults.…”
Section: Introductionmentioning
confidence: 98%
“…When looking at the specific results of the n-back tasks, one can see that the 1-back task has been performed more accurately than the 2-back task suggesting a higher executive load of the 2-back task (see also Jaeggi et al 2009). Performing the secondary task with higher executive load disrupted advantageous decision-making, whereas performing the secondary task with lower executive load did not lead to a significant deterioration in decision-making.…”
Section: Discussionmentioning
confidence: 94%
“…S2) [hits: t(31) = 1.45; P = 0.16; false alarms: t(31) = 0.93; P = 0.36, calculated as gain subtracting the mean RT of the individual last two training sessions from the mean RT in the first two training sessions]. Of course, the numerical increase in RT is most likely driven by the increasing level of n on which participants trained (35). Thus, to control for difficulty, we calculated regression models for each participant as a function of nback level using RT as the dependent variable, and session as the independent variable.…”
Section: Discussionmentioning
confidence: 99%